Prognostic Value of Thyroid Hormone Ratio in Patients With Advanced Metastatic Renal Cell Carcinoma: Results From the Threefour Study (Meet-URO 14) - Maruzzo, Marco; Verzoni, Elena; Vitale, Maria Giuseppa; Dionese, Michele; Buti, Sebastiano; Galli, Luca; Zivi, Andrea; Watutantrige-Fernando, Sara; Zielli, Teresa; Zanardi, Elisa; Sabbatini, Roberto; Basso, Umberto; et al. (Frontiers in Oncology, 2021)
Background: Thyroid hormone impairment, represented as an alteration in levels of thyroid hormones and a lower fT3/fT4 ratio, has been correlated with a worse prognosis for both cancer and non-cancer patients. The role of baseline thyroid function in patients with metastatic renal cell carcinoma (mRCC) however, has not been studied yet. Materials and methods: We recorded clinical data, baseline biochemical results, and oncological outcomes from 10 Oncology Units in Italy. We stratified patients into three groups according to the fT3/fT4 ratio value and subsequently analyzed differences in progression-free survival (PFS) and overall survival (OS) in the three groups. We also performed univariate and multivariate analyses to find prognostic factors for PFS and OS. Results: We analyzed 134 patients treated with systemic treatment for mRCC. Median PFS in the low, intermediate, and high fT3/fT4 ratio group were 7.5, 12.1, and 21.7 months respectively (p<0.001); median OS in the three groups were 36.5, 48.6, and 70.5 months respectively (p =0.006). The low fT3/fT4 ratio maintained its prognostic role at the multivariate analysis independently from IMDC and other well-established prognostic factors. The development of iatrogenic hypothyroidism was not associated with a better outcome. Conclusion: We found that baseline thyroid hormone impairment, represented by a low fT3/fT4 ratio, is a strong prognostic factor in patients treated for mRCC in first line setting and is independent of other parameters currently used in clinical practice.